Towards Power Relationship Dynamics and Community Smells in the Proprietary Software Ecosystem - Ribeiro, Bárbara Beato; Costa, Luiz Alexandre; Outão, Juliana Carvalho Silva Do; Santos, Rodrigo Pereira Dos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
A Proprietary Software Ecosystem (PSECO) comprises a common technological platform with contributions protected by intellectual property. The social aspects of software development in a PSECO involve iterations in different scenarios, such as collaboration, teamwork, and productivity. Power relationships among actors within an ecosystem are a key social aspect. They may cause community smells, i.e., unforeseen socio-technical events that may result in additional costs to the project. If social aspects are recognized especially in PSECO, the IT management team may develop governance strategies to deal with them. This work investigates power relationships and community smells in PSECO, focusing on one of their components: actors. To identify the existing community smells, a systematic mapping study was performed. Results revealed that social aspects are barely explored in PSECO. Such opportunity motivated us to explore power relationships dynamics in PSECO through a focus group. The focus group raised 17 power relationship dynamics in PSECO. Our work highlighted behavioral issues in PSECO related to community smells and power relationships.